Neuroprotective Activity Of Hydroalcoholic Extract Of Fruits Of Punica Granatum Against Aluminium Chloride Induced Alzheimer In Rats. (International Journal of Food and Nutritional Sciences, 2022)
This study investigated the neuroprotective effects of hydroalcoholic extracts of fruits Punica granatum (HAEPG 100 and HAEPG 200 mg/kg) on learning and memory in rats with Alzheimer's disease (AD) induced by aluminium chloride (AlCl3). All Wistar rats in groups II to IV received the appropriate treatment dosages (100/200 mg/kg) 30 minutes prior to the oral administration of aluminium chloride (100 mg/kg), which was administered daily for 42 days. Rats' gross behavioural activity was assessed using an open field arena (OFA) on days 20, 21, and 42 after the beginning of the administration of aluminium chloride. Line crossing, centre square entries, rearing, and grooming were used to score behavioural performance.Morris Water Maze (MWM) and the Elevated Plus Maze (EPM) were used to assess cognitive performance. On days 19 and 20, MWM-rats were trained to swim to a platform in a circular pool. It was determined how long it took to get to the visual platform (acquisition latency). The first retention latency (1 RL) (21 day) and the second retention latency (2 RL) (42 day) were measured as the amount of time it took to identify the hidden platform after the first day of aluminium chloride administration. On day 20, EPM-rats were trained, and each rat was placed at the end of an open arm. The initial transfer latency, which measures the time taken by the rat to go from the end of the open arm to either of the closed arms, was then recorded (ITL). The rats were examined for retention latency on days 21 and 42, and the results were referred to as first RTL and second RTL, respectively. According to data from OFA, MWM, and EPM, the corresponding treatment groups (100/200 mg/kg, p.o.) significantly defended against Alzheimer's disease caused by aluminium chloride.